In-Frame and Frame-Shift Editing of the Ehd1 Gene to Develop Japonica Rice With Prolonged Basic Vegetative Growth Periods - Wu, Mingji; Liu, Huaqing; Lin, Yan; Chen, Jianmin; Fu, Yanping; Luo, Jiami; Zhang, Zhujian; Liang, Kangjing; Chen, Songbiao; Wang, Feng (Frontiers in Plant Science, 2020)
Japonica rice has become increasingly popular in China owing to its superior grain quality. Over the past decades, “indica to japonica” projects have been proposed to promote cultivation of japonica rice in low latitudes in China. Traditionally, japonica varieties were planted mainly in mid latitudes in the northeast plain and Yangtze River region. The key obstacle for introducing elite mid-latitude japonica varieties to low latitudes is the severe shortening of growth period of the japonica varieties due to their sensitivity to low-latitude short photoperiod and high temperature. Here we report development of new japonica rice with prolonged basic vegetative growth (BVG) periods for low latitudes by targeted editing the Early heading date 1 (Ehd1) gene. Using CRISPR/Cas9 system, we generated both frame-shift and/or in-frame deletion mutants in four japonica varieties, Nipponbare, Longdao16, Longdao24, and Xiushui134. When planting at low-latitude stations, the frame-shift homozygous lines exhibited significantly longer BVG periods compared with wild-types. Interestingly, we observed that minor deletion of the first few residues within the receiver domain could quantitatively impair the function of Ehd1 on activation of Hd3a and RFT1, resulting in an intermediate-long BVG period phenotype in the homozygous in-frame deletion ehd1 lines. Field investigation further showed that, both the in-frame and frame-shift lines exhibited significantly improved yield potential compared with wild-types. Our study demonstrates an effective approach to rapid breeding of elite japonica varieties with intermediate-long and long BVG periods for flexible cropping systems in diverse areas or under different seasons in southern China, and other low-latitude regions.